SIMBOLISASI PEMIMPIN DALAM KARYA SENI GRAFIS RELIEF PRINT - Putri Ayu Hayati; Yofita Sandra (Universitas Negeri Padang, 2020)
This work produced through various processes and inspired by many social phenomena. In making this work the authors chose a theme related to social criticism. The author presents symbol of leadership. In the final work the author uses the technique of relief print which is also called the relief print and linoleum rubber as the cliché. The process done by removing unneeded parts, the highest surface part which is not carved into a will transfered the pigment. From the processes ofrelief print making, the creators has entitled: illuminting and hurting, dolls, pens, protect, pointers, struggles, infrastructure, steps of progress, deciding and skippers.Keywords: leader symbol, relief print